2009
DOI: 10.1186/1471-2342-9-17
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal volumes are important predictors for memory function in elderly women

Abstract: BackgroundNormal aging involves a decline in cognitive function that has been shown to correlate with volumetric change in the hippocampus, and with genetic variability in the APOE-gene. In the present study we utilize 3D MR imaging, genetic analysis and assessment of verbal memory function to investigate relationships between these factors in a sample of 170 healthy volunteers (age range 46–77 years).MethodsBrain morphometric analysis was performed with the automated segmentation work-flow implemented in Free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 64 publications
(68 reference statements)
8
70
0
2
Order By: Relevance
“…6A). Since a number of studies have shown that hippocampal volume affects memory functions (29), forced mastication due to a hard diet may be able to indirectly improve memory. For an assessment of neural activity after forced mastication, the expression of c-Fos in the DG of the group fed the hard diet and the group fed the normal diet was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…6A). Since a number of studies have shown that hippocampal volume affects memory functions (29), forced mastication due to a hard diet may be able to indirectly improve memory. For an assessment of neural activity after forced mastication, the expression of c-Fos in the DG of the group fed the hard diet and the group fed the normal diet was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…All the participants were subject to a neuropsychological examination and to multimodal imaging. One of the expected outcomes of the study is to understand the relations between imagederived features of the brain and cognitive functions in healthy aging [7]. The study involves 3D anatomical magnetic resonance imaging (MRI) of the brain, followed by diffusion tensor imaging (DTI) and resting state functional MRI in the same imaging session [12] [13].…”
Section: Interactive Visual Analysis Environmentmentioning
confidence: 99%
“…We analyze the data from a longitudinal study of cognitive aging where the participants were chosen among healthy individuals [6] [7]. All the participants were subject to a neuropsychological examination and to multimodal imaging.…”
Section: Interactive Visual Analysis Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Espeseth et al (2012) link APOE-related changes of cortical thickness to variation in attention. Ystad et al (2009) used both Sonata and GE Signa data to study APOE effects on hippocampal volumes and relations with memory functions. Westlye et al (2011) recently published a study revealing effects of APOE on resting-state connectivity based on the GE Signa data.…”
Section: Mri-based Imagingmentioning
confidence: 99%